Reconstruction of a source of Ibn Isḥaq's life of the Prophet and early Qurʼan exegesis: a study of early Ibn ʻAbbas traditions - Motzki, Harald (Islamic history and thought, 2017)
The problem of sources on the life of the Prophet Muḥammad -- Source analysis -- A reaction of the Quraysh to Muḥammad's rise -- Muḥammad b. Abī Muḥammad -- The profile of the source "Muḥammad b. Abī Muḥammad" -- Muḥammad b. Abī Muḥammad outside of the Sīra sources -- Narrations without parallels in Ibn Hishām's Sīra -- Al-Kalbī's variants -- Muḥammad b. Abī Muḥammad's sources -- Muḥammad b. Abī Muḥammad: a source for the historical vita of the Prophet? -- Excursus: Ibn Isḥāq's exegetical traditions from Muḥammad b. Abī Muḥammad -- Appendix: Isnāds of the most important traditions